PHOTODYNAMIC INACTIVATION OF PATHOGENIC BACTERIA IN BIOFILMS USING NEW SYNTHETIC BACTERIOCHLORIN DERIVATIVES - I. G. Tiganova; E. A. Makarova; G. A. Meerovich; N. V. Alekseeva; E. R. Tolordava; Yu. S. Zhizhimova; E. A. Lukyanets; Yu. M. Romanova (Biomedical Photonics)
Bacteriochlorins as the antimicrobial photosensitizers have a promising future in the face of the unrelenting increase in antimicrobial resistance. The goal of this study was to investigate the infl uence of lipophilicity and number of positively charged  substituents in these molecules on the photodynamic inactivation  (PDI) of biofi lm bacteria in vitro. Testing how bacteriochlorin  derivatives with different properties affect microbes will allow to  determine the optimal ratio of these parameters within a single  molecule. We have investigated 4 bacteriochlorin derivatives, all of  which were synthesized in Organic Intermediates and Dyes Institute. These were: hydrophobic neutral meso-tetra(3-pyridyl)  bacteriochlorin (ВС1), amphyphilic tetracationic meso-tetra(1- undecyl-3-pyridyl)bacteriochlorin tetrabromide (ВС2), hydrophilic  tetracationic meso-tetra[1-(4'-bromobutyl)-3-pyridyl]bacteriochlorin  tetrabromide (ВС3) and octacationic meso-tetra[1-(4'-pyridiniobutyl) -3-pyridyl]bacteriochlorin octabromide (ВС4) . The water-soluble  cationic bacteriochlorin derivatives showed the most effective PDI of  bacteria in biofi lms. While tetracationic BC3 caused total inactivation of S. aureus 15, octacationic BC4 was bactericidal for P. aeruginosa  32 to the same degree (>99.999%). Interestingly, increasing the  number of cationic substituents from 4 to 8 in bacteriochlorin  molecules enhances bactericidal action against gram-negative  bacteria in biofi lms. The lack of charge-carrying groups and high  degree of lipophilicity of PS have negative impact on PDI of biofi lm  bacteria. Bacterial membrane damage as a result of PDI can be one of the causes of cell death.